2014
DOI: 10.1213/ane.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Topical Combinations to Treat Microvascular Dysfunction of Chronic Postischemia Pain

Abstract: The present results support the hypothesis that allodynia in an animal model of CRPS is effectively relieved by topical combinations of α2A receptor agonists or NO donors with PA or PDE inhibitors. This suggests that topical treatments aimed at improving microvascular function by increasing both arterial and capillary blood flow produce effective analgesia for CRPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We speculate that the recent failure of tadalafil to elevate limb temperature [37] is the result of capillary dysfunction, which causes a dissociation between tissue oxygenation on one hand, and limb blood flow/ temperature on the other. Studies in a post-ischemic pain model confirm that systemic PDE [46], as well as topical PDE application either alone or in combination with vasodilators [37], relieve allodynia while reversing the suppression of flow responses [31], consistent with a role of elevated CTH and tissue hypoxia in this model.…”
Section: Discussionsupporting
confidence: 56%
“…We speculate that the recent failure of tadalafil to elevate limb temperature [37] is the result of capillary dysfunction, which causes a dissociation between tissue oxygenation on one hand, and limb blood flow/ temperature on the other. Studies in a post-ischemic pain model confirm that systemic PDE [46], as well as topical PDE application either alone or in combination with vasodilators [37], relieve allodynia while reversing the suppression of flow responses [31], consistent with a role of elevated CTH and tissue hypoxia in this model.…”
Section: Discussionsupporting
confidence: 56%
“…Additonally, it was previously reported that MG inhibited ET-1 secretion and restored the loss of NO production when cells were exposed to high glucose under endoplasmic reticulum stress conditions ( Song et al, 2015 ). An earlier study of the CPIP model revealed that topical combinations including α 2A receptor agonists, phosphodiesterase four inhibitors, or NO donors improved both arterial and capillary blood flow associated with effective analgesia ( Ragavendran et al, 2013 ; Laferrière et al, 2014 ). All these facts add support to our interpretation that MG relaxant properties may be closely related to the activation of the NO-cGMP pathway in CPIP.…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline is a drug with multiple mechanisms of action that has been typically used in vascular claudication to improve microcirculatory blood flow and thus reduce the symptoms of tissue ischemia (Laferriere et al, 2014). In more recent times, pentoxifylline has demonstrated widespread neuroinflammatory effects of a potentially beneficial nature in pain models (Liu et al, 2007).…”
Section: Dear Editormentioning
confidence: 99%